2014
DOI: 10.3390/rel5030703
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Level of Strictness and Congregational Growth

Abstract: Abstract:Beginning with Kelley's and Iannaccone's foundational studies, scholars have examined how strictness impacts congregational outcomes. This paper seeks to further develop the strict church thesis by examining Iannaccone's concept of "optimal level of strictness", an idea that there are limits to strictness. Using Stark and Finke's theoretical framework of religious niches and data from the 2005 Baylor Religion Survey and the 2000 Faith Communities Today survey, I find that only prohibitions that are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…found on the CoS official Twitter page, where Gilmore attacks religious beliefs (and individuals) directly on a near daily basis. By setting the CoS also at odds with the external society Gilmore begins utilizing niche preference (Ferguson 2014) by catering to the core constituency at higher tension with the rest of religious America, leading to greater attractiveness to would be converts and higher internal commitment. This strategy for growth by CoS is mirrored by the relative ease of acquiring active membership in CoS now in comparison to the 1970s.…”
Section: Environment/niche Impactmentioning
confidence: 99%
“…found on the CoS official Twitter page, where Gilmore attacks religious beliefs (and individuals) directly on a near daily basis. By setting the CoS also at odds with the external society Gilmore begins utilizing niche preference (Ferguson 2014) by catering to the core constituency at higher tension with the rest of religious America, leading to greater attractiveness to would be converts and higher internal commitment. This strategy for growth by CoS is mirrored by the relative ease of acquiring active membership in CoS now in comparison to the 1970s.…”
Section: Environment/niche Impactmentioning
confidence: 99%
“…All of this can be obtained if the individual submits to the Pentecostal/Charismatic rules, even if the individual does not have any educational or financial resources at her disposal. ‐ Strictness . Inspired by Kelley ([1972] ), a number of authors have suggested that EFPC groups have an edge over their mainline competitors due to their higher level of strictness (Ferguson ; Iannaccone ; Olson and Perl, , ; Thomas and Olson ). The definition of strictness and the exact formulation of the mechanism vary between different authors, but the overall idea is as follows: the strictness of a group is the extent to which it is able to impose norms and make demands vis‐à‐vis its leaders and members.…”
Section: Theorymentioning
confidence: 99%
“…As Iannaccone (:1,202) notes, there must be an optimal level of strictness, as extreme strictness will prove so costly for members that many will eventually drop out and new converts will be scared away. On this point, see Ferguson (). On the Iannaccone paper, see also Marwell () and the reply by Iannaccone ().…”
mentioning
confidence: 99%
“…The demands that evangelicalism make are not merely strict, they are also framed and reframed in ways that accommodate the church's relationship to the ever‐changing realities of modern life. Finally, Ferguson () used culture to determine the optimal level of strictness for a congregation, finding that only strictness that is congruent with a congregation's “religious niche” impacts its growth.…”
Section: Theoretical Backgroundmentioning
confidence: 99%